The Influence of Social Assistance and Education on Poverty Rates through GRDP in Papua Province in 2018-2022 - Dzahira Safitri (Universitas Negeri Semarang, 2024)
The purpose of conducting this research was to determine the effect of social assistance on poverty rates through economic growth in 29 urban districts in Papua province in 2018-2022. Research data uses panel data obtained from the Central Bureau of Statistics with research objects of 29 urban districts in the province of Papua. The research method used is path analysis. The research results show that cash food assistance and the Smart Indonesia program have no effect on poverty levels. While direct cash assistance has a significant negative effect on the level of poverty.